Heart Failure Association of the European Society of Cardiology heart failure nurse curriculum - Riley, Jillian P.; Astin, Felicity; Crespo-Leiro, Marisa G.; Deaton, Christi M.; Kienhorst, Jens; Lambrinou, Ekaterini; McDonagh, Theresa A.; Rushton, Claire A.; Stromberg, Anna; Filippatos, Gerasimos; Anker, Stefan D. (My University, 2016)
Recent advances in care and management of heart failure have improved outcome, largely as a result of the developing evidence basis for medications, implantable devices and the organization of heart failure follow-up. Such developments have also increased the complexity of delivering and coordinating care. This has led to a change to the way in which heart failure services are organized and to the traditional role of the heart failure nurse. Nurses in many countries now provide a range of services that include providing care for patients with acute and with chronic heart failure, working in and across different sectors of care (inpatient, outpatient, community care, the home and remotely), organising care services around the face-to-face and the remote collection of patient data, and liaising with a wide variety of health-care providers and professionals. To support such advances the nurse requires a skill set that goes beyond that of their initial education and training. The range of nurses' roles across Europe is varied. So too is the nature of their educational preparation. This heart failure nurse curriculum aims to provide a framework for use in countries of the European Society of Cardiology. Its modular approach enables the key knowledge, skills, and behaviours for the nurse working in different care settings to be outlined and so facilitate nursing staff to play a fuller role within the heart failure team.
Keywords: Education; Heart failure; Heart failure nurse; Multidisciplinary team